2022
DOI: 10.33448/rsd-v11i4.26426
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation among university students during the COVID-19 pandemic: a rapid systematic review with meta-analysis

Abstract: The COVID-19 pandemic brought several behavioral changes in the social, academic and professional spheres, caused numerous deaths and, due to the lack of treatment, imposed social isolation and an adaptation of daily activities, restricted to the remote format, causing emotional and mental instability. in society. Thus, this study aimed to investigate the prevalence of suicidal ideation and associated factors among university students during the COVID-19 pandemic. A Rapid Systematic Review was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…We can see an increase in ideation if we compare their percentage with ours. The increase may reflect a general trend over the past years in China and may reflect the long-term social and economic disruptions caused by the COVID-19 pandemic [72,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can see an increase in ideation if we compare their percentage with ours. The increase may reflect a general trend over the past years in China and may reflect the long-term social and economic disruptions caused by the COVID-19 pandemic [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…This pandemic has caused large-scale disruptions including depression, anxiety, and stress. Although recent studies have not observed an increase in suicide rates in the first months of the pandemic [75][76][77][78], it has been reported that disruptions caused by the pandemic, including depression and anxiety, are important factors associated with suicidal ideation and behavior in college students [72,73] and adults [79][80][81]. Future studies are needed to examine the long-term impact of the pandemic on suicide [75][76][77]82].…”
Section: Discussionmentioning
confidence: 99%
“…3,10,11 Several reviews found that university students were at high risk for suicide-related behaviours, and associated risk factors included social isolation and mental illness. [11][12][13] As the long-term mental health effects of the COVID-19 pandemic are unclear, continued surveillance is needed to inform comprehensive and effective responses to suicide risks, including among young adults.…”
Section: Introductionmentioning
confidence: 99%